2020
DOI: 10.1177/0300060520923878
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of the efficacy and safety of adjunctive alpha-blocker therapy before ureteroscopy in the management of ureteral stones

Abstract: Objective To evaluate the efficacy and safety of adjunctive alpha-blocker therapy before ureteroscopy in the management of ureteral stones. Methods The databases MEDLINE®, EMBASE and The Cochrane Controlled Trail Register of Controlled Trials were searched between January 1980 and June 2019 to identify randomized controlled trials (RCTs) that referred to the use of alpha-blockers as adjunctive therapy before ureteroscopy for the treatment of ureteral stones. Odds ratios (ORs) with 95% confidence intervals (CIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…However, in this analysis, contrary to our findings, no significant difference in the operation time between the two groups was found. 18 In 2018, Mohey et al, published a study, 19 that showed the results that were comparable to ours in which pre-operative alpha blockade was achieved with 8mg of Silodosin. During URS, the group that received Silodosin was found that advancement of ureteroscope was much easier which made access to the stone also easier.…”
Section: Discussionsupporting
confidence: 79%
“…However, in this analysis, contrary to our findings, no significant difference in the operation time between the two groups was found. 18 In 2018, Mohey et al, published a study, 19 that showed the results that were comparable to ours in which pre-operative alpha blockade was achieved with 8mg of Silodosin. During URS, the group that received Silodosin was found that advancement of ureteroscope was much easier which made access to the stone also easier.…”
Section: Discussionsupporting
confidence: 79%
“…12 It is challenging and risky to advance a ureteroscope into the non-dilated ureter; failure to do might result in the procedure's failure. 13 A systematic review by Rob S, et al showed equally high SFRs and safety profiles of URS in pediatrics may be attained by medium-volume centers as well as large-volume centers, hence encouraging expanded URS use in facilities that do fewer operations annually. 14 According to meta analysis from Ziaeefar, using medical compulsive therapy (MET) enhances stone expulsive rate while decreasing stone expulsive time.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the placebo group, the adjunctive alpha-blocker medication was linked to a considerably reduced risk of all these complications. 13 A meta analysis by Sesari SS, et al showed that administration of adjunctive alpha blocker also minimizes colic episodes. 23 In children, the lumens of the ureters are narrow, making ureteroscopy has many failures compared to adults, thus providing a more complex challenge.…”
Section: Discussionmentioning
confidence: 99%
“…10 Medical expulsive therapy (MET) should be considered for ureterolithiasis with positive outcomes for ureteroscopy following preoperative alpha-blockers showing significant reduction for the need of ureteral orifice dilation 11 and higher rate of access to stones. 12 None have evaluated medication use in material entrapment as it is a rare situation. In our case, patient did not receive alpha-blockers prior to surgery.…”
Section: Discussionmentioning
confidence: 99%